Pharmacokinetics and Brain Distribution of the Active Components of DA-9805, Saikosaponin A, Paeonol, and Imperatorin in Rats - Mi Hye Kwon; Jin Seok Jeong; Jayoung Ryu; Young Woong Cho; Hee Eun Kang (MDPI AG, 2018)
DA-9805 is a botanical anti-Parkinson’s drug candidate formulated from ethanol extracts of the root of Bupleurum falcatum, the root cortex of Paeonia suffruticosa, and the root of Angelica dahurica. The pharmacokinetics (PKs) and brain distribution of active/representative ingredients of DA-9805, Saikosaponin a (SSa; 1.1–4.6 mg/kg), Paeonol (PA; 14.8–59.2 mg/kg), and Imperatorin (IMP; 1.4–11.5 mg/kg) were evaluated following the intravenous or oral administration of each pure component and the equivalent dose of DA-9805 in rats. All three components had greater dose-normalized areas under the plasma concentration-time curve (AUC) and slower clearance with higher doses, following intravenous administration. By contrast, dose-proportional AUC values of SSa, PA, and IMP were observed following the oral administration of each pure component (with the exception of IMP at the highest dose) or DA-9805. Compared to oral administration of each pure compound, DA-9805 administration showed an increase in the AUC of SSa (by 96.1–163%) and PA (by 155–164%), possibly due to inhibition of their metabolism by IMP or other component(s) in DA-9805. A delay in the absorption of PA and IMP was observed when they were administered as DA-9805. All three components of DA-9805 showed greater binding values in brain homogenates than in plasma, possibly explaining why the brain-to-plasma ratios were greater than unity following multiple oral administrations of DA-9805. By contrast, their levels in cerebrospinal fluid were negligible. Our results further our understanding of the comprehensive PK characteristics of SSa, PA, and IMP in rats and the comparative PKs between each pure component and DA-9805.